A landscape level analysis of entrepreneurship and sustainable energy transitions: Evidences from Gujarat, India. (5th October 2021) - Haldar, Stuti
Abstract: In accordance with India's sustainable energy targets of achieving 175 GW of renewable energy (RE) installed capacity by 2022 and 450 GW by 2030, the role of private sector actors has become increasingly important. As presently, 96 percent of the total installed RE utilities in India are privately owned; this makes sustainability driven entrepreneurship the core of India's energy sector transition. It is vital to explore various individual and firm level, policy and market related factors that enable entrepreneurs to induce innovative RE technologies in the existing conventional energy regime in India. So, this study adopts a multi‐level perspective approach to understand what and how processes at the landscape level (national, sub‐national policy, and international concerns) interplay with niche (sustainability driven entrepreneurs) and regime (existing fossil fuel regime) to create windows of opportunities for sociotechnical transition from conventional to clean energy. This empirical study incorporates structured interviews with 54 RE entrepreneurs operating in Gujarat, to understand the role of policy and international factors in facilitating innovation and firm growth in this sector. As Gujarat contributes around 12 percent to the total RE basket in India and with its culture of innovation and entrepreneurship, ranks among the top 10 states in terms of Ease of Doing Business (2019) the study area has been delimited to this Indian state. The study finds that despite having policy regulations such as tax incentives, Renewable Purchase Obligations, safe‐guard duties, and financial subsidies to promote innovation and entrepreneurship in the RE sector, the profitability of these entrepreneurs is low. Moreover, there are loopholes in implementation of policies which further impede growth of RE entrepreneurship hence leading to hindrance in adoption and diffusion of clean energy technologies in India.